1004 How Variable Is Sleep?. (12th April 2019) - Gunter, Paul W; Bassi, Massimo A; Ikromova, Masha; Tsao, Jonathan; Gehrman, Philip
Abstract: Introduction: Sleep patterns are often described in terms of the average over a 1-2 week period of assessment with either self-report (e.g. sleep diary) or objective (e.g. actigraph) assessment. In recent years, there has been greater interest in the variability in sleep over time, but variability has mainly been studied using short-term "snippets" of data spread out longitudinally. There is a need for longer-term monitoring in order to better understand the extent to which sleep patterns are stable/unstable in individuals over time. One approach is to utilize "smart" mattress sensor technology that can assess sleep unobtrusively over long periods of time. The present study examined variability in sleep over periods up to a year using sleep efficiency assessed with mattress sensors as a global index of sleep quality. Methods: Data were from users of the Eight Sleep mattress, which collects and integrates data from multiple sensors to estimate sleep/wake patterns. Nights were categorized as "good" and "bad" nights using a cutoff of 85%. Descriptive statistics were computed to describe both individual means as well as variability across nights. Pearson's correlations were conducted between means and standard deviations of individuals' sleep efficiencies. Results: The sample consisted of 100 mattress users who had valid data from 151 to 978 nights. The mean sleep efficiency across individuals was 73.20%, with a mean standard deviation of 20.53%. 59.61% of nights were classified as good nights, and 40.39% were poor. The mean (SD) coefficient of variation was .29 (0.11), with a range of 0.12 to 0.71, indicating a wide range of variability. There was a significant correlation between individuals' mean and standard deviation in sleep efficiency ( r = -.71, p < .01), such that higher mean sleep efficiency was associated with less variability. Conclusion: When examined over longer periods of time, there is considerable variability in sleep efficiency both within and between individuals. Individuals with poorer sleep overall also tend to have more variable sleep over time. "Smart" mattress pads are a pragmatic tool that can be used to gather large amounts of continuous, longitudinal sleep data. Support (If Any): None.